The Treatment of Sleep Disorders in Parkinson’s Disease: From Research to Clinical Practice - Loddo, Giuseppe; Calandra-Buonaura, Giovanna; Sambati, Luisa; Giannini, Giulia; Cecere, Annagrazia; Cortelli, Pietro; Provini, Federica (Frontiers in Neurology, 2017)
Sleep disorders (SDs) are one of the most frequent non-motor symptoms of Parkinson’s disease (PD), usually increasing in frequency over the course of the disease and disability progression. SDs include nocturnal and diurnal manifestations such as insomnia, REM sleep behavior disorder and excessive daytime sleepiness. The causes of sleep disorders in PD are numerous, including the neurodegeneration process itself, which can disrupt the networks regulating the sleep-wake cycle and deplete a large number of cerebral amines possibly playing a role in the initiation and maintenance of sleep. Despite the significant prevalence of SDs in PD patients, few clinical trials on SDs treatment have been conducted. Our aim is to critically review the principal therapeutic options for the most common SDs in PD. The appropriate diagnosis and treatment of SDs in PD can lead to the consolidation of nocturnal sleep, the enhancement of daytime alertness and the amelioration of the quality of life of the patients.